Flow Alignment of Extracellular Vesicles: Structure and Orientation of Membrane‐Associated Bio‐macromolecules Studied with Polarized Light. (7th February 2018) - Szigyártó, Imola Cs.; Deák, Róbert; Mihály, Judith; Rocha, Sandra; Zsila, Ferenc; Varga, Zoltán; Beke‐Somfai, Tamás
Abstract: Extracellular vesicles (EVs) are currently in scientific focus, as they have great potential to revolutionize the diagnosis and therapy of various diseases. However, numerous aspects of these species are still poorly understood, and thus, additional insight into their molecular‐level properties, membrane–protein interactions, and membrane rigidity is still needed. We here demonstrate the use of red‐blood‐cell‐derived EVs (REVs) that polarized light spectroscopy techniques, linear and circular dichroism, can provide molecular‐level structural information on these systems. Flow‐linear dichroism (flow‐LD) measurements show that EVs can be oriented by shear force and indicate that hemoglobin molecules are associated to the lipid bilayer in freshly released REVs. During storage, this interaction ceases; this is coupled to major protein conformational changes relative to the initial state. Further on, the degree of orientation gives insight into vesicle rigidity, which decreases in time parallel to changes in protein conformation. Overall, we propose that both linear dichroism and circular dichroism spectroscopy can provide simple, rapid, yet efficient ways to track changes in the membrane–protein interactions of EV components at the molecular level, which may also give insight into processes occurring during vesiculation. Abstract : Polarized light spectroscopy techniques, which are commonly used on model liposomes in biophysical and structural chemistry studies, can provide important information on red‐blood‐cell‐derived extracellular vesicles. The Soret band of linear dichroism spectra gives insight into the distribution and relative orientation of hemoglobin complexes associated to membrane components.